Educators and students perceptions about Ecuadorian NEST knowledge and quality in terms of effective teaching - Sevy-Biloon, Julia (Penerbit Universiti Kebangsaan Malaysia, 2017)
EFL has become necessary in all areas of education over the last decade in Ecuador. There has been a widespread push for changes in the level of knowledge and quality of EFL teacher effectiveness throughout the educational system. This paper aims to look at what perceptions current EFL participants have about the Ecuadorian NNEST and if they have the necessary linguistic awareness, language skills and teaching qualities to teach EFL effectively. The data for this investigation includes 89 student questionnaires and 30 teacher interviews based on their perceptions. The findings illustrated how students at lower levels tend to be more comfortable with teachers who use primarily the first language (L1) and have effective teaching qualities, while upper intermediate students tended to choose NESTs, because they needed proficiency skills such as language fluency and high levels of oral communication to be examples in class. The study goes onto demonstrate how many Ecuadorian NNESTs cannot speak, understand, communicate or pronounce English fluently at higher levels since many did not have teachers who possessed these qualities. This phenomenon creates the perception that a native speaker will have better fluency, pronunciation and overall better proficiency than an Ecuadorian NNEST. These results show it is necessary for these teachers to increase their English proficiency to be effective teachers in the future and change the perception that native speakers have higher levels of English in Ecuador.